Optimization of Thermosiphon Solar Water Heaters working in a Mediterranean Environment - Kalogirou, Soteris A.; Agathokleous, Rafaela (My University, 2013)
Cyprus is currently the leading country in the world with respect to solar water heaters installations. The increase of the thermosiphon solar water heaters usage over the last years makes this subject to be very important for further investigation. The main objective of this study is to investigate the parameters affecting the system’s performance in order to find the optimum design to increase the performance of the system. For this purpose, a number of riser and header tube diameters were considered ranging from 6 mm to 35 mm, slopes from latitude from 20° to 90°, distances between the top of the collector to the bottom side of the storage tank ranging from -30 to +20 cm and the vertical or horizontal tank position. The system is modelled using TRNSYS and simulated with the Typical Meteorological Year (TMY) of Nicosia, Cyprus. It was observed that, the current typical system is not the optimum case and its operation can be further improved. The optimum system obtained from the simulations has a flat plate collector with header pipe of 22 mm and 20 riser pipes of 8 mm diameter, sloped at 40° and the distance between the top of the collector and the bottom of the storage tank is -20 cm. These findings should prove valuable for the collector and systems designers and manufacturers.
Keywords: Thermosiphon; Flat plate collector; Riser tubes; Solar water heater; Optimization; Solar thermal